2021
DOI: 10.1002/anie.202108589
|View full text |Cite
|
Sign up to set email alerts
|

Ring Expansion Fluorination of Unactivated Cyclopropanes Mediated by a New Monofluoroiodane(III) Reagent

Abstract: Herein, we report anew strategy for carbon À carbon bond scission and intramolecular ring expansion fluorination of unactivated cyclopropanes,w hichw as accomplished with an ew hypervalent fluoroiodane(III) reagent 1.T his novel method delivers medicinally relevant 4-fully substituted fluoropiperidines in moderate to high yields with excellent regioand diastereoselectivity.Reagent 1,which has an N-acetylbenziodazole framework, was readily synthesized via three steps in 76 %o verall yield and was characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…DFT studies revealed that the mechanism proceeds through a carbocationic intermediate (Scheme 47). 105…”
Section: Synthesis and Functionalisation Of Heterocycles Using Hyperv...mentioning
confidence: 99%
See 1 more Smart Citation
“…DFT studies revealed that the mechanism proceeds through a carbocationic intermediate (Scheme 47). 105…”
Section: Synthesis and Functionalisation Of Heterocycles Using Hyperv...mentioning
confidence: 99%
“…DFT studies revealed that the mechanism proceeds through a carbocationic intermediate (Scheme 47). 105 As per the suggested mechanism, initially, the hypervalent species The Wengryniuka group in 2021, reported an efficient method that provides access to functionalised chromanes (78) from primary, secondary, and tertiary alcohols via cyclisation followed by iodonium salt formation (Scheme 49). 106 The He group reported an effective method for the aminolactonisation of unactivated alkenes (79) via aryl-iodine catalysis, in which diverse amino lactones (80) are constructed in a short time using HNTs 2 as the compatible nitrogen source.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…ORTEP drawings of 3fand 3s with thermal ellipsoids at 50 %p robability. [25] Angewandte Chemie Forschungsartikel substrates 2s' ', 2t' ' were tried, the reaction still proceeded well and afforded desired products 3s' ', 3t' ' in 86 %and 87 %yield, respectively.T he structures and stereochemistries of these products were established by 1 HNMR and nuclear Overhauser effect experiments (see the SI for details). Furthermore,weconfirmed that the cis isomer was the major product by means of single-crystal X-ray diffraction analysis of 3s (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
“…Benziodazolone compounds 2 , nitrogen analogs of benziodoxolones, are also known and offer the possibility of fine-tuning the reactivity by modifying the substituent on the nitrogen atom [ 20 , 21 , 22 , 23 ]. Thus, a number of reagents of 2 with various nitrogen-containing ligands and functional groups have been developed [ 24 , 25 , 26 , 27 , 28 ]. For example, benziodazolone compounds 2 supported by various ligands are known as atom-transfer reagents and can act as very effective electrophilic reagents for a variety of substrates, including azidation [ 20 ], alkynylation [ 24 ], and trifluorothiomethylation reagents [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, benziodazolone compounds 2 supported by various ligands are known as atom-transfer reagents and can act as very effective electrophilic reagents for a variety of substrates, including azidation [ 20 ], alkynylation [ 24 ], and trifluorothiomethylation reagents [ 25 ]. Very recently, Zhang and coworkers investigated the synthesis and structural characterization of a stable fluorobenziodazolone compound and demonstrated that the novel reagent can efficiently perform ring-extended fluorination reactions for various three-membered ring compounds [ 26 ]. In addition, benziodazolones 3 are also capable of working as oxidants in dehydrogenative coupling reactions between various two-component molecules [ 27 ].…”
Section: Introductionmentioning
confidence: 99%